Step
*
1
1
of Lemma
disjoint_sublists_witness
.....assertion..... 
1. [T] : Type
2. L1 : T List
3. L2 : T List
4. L : T List
5. f1 : ℕ||L1|| ⟶ ℕ||L||
6. f2 : ℕ||L2|| ⟶ ℕ||L||
7. increasing(f1;||L1||)
8. ∀j:ℕ||L1||. (L1[j] = L[f1 j] ∈ T)
9. increasing(f2;||L2||)
10. ∀j:ℕ||L2||. (L2[j] = L[f2 j] ∈ T)
11. ∀j1:ℕ||L1||. ∀j2:ℕ||L2||.  (¬((f1 j1) = (f2 j2) ∈ ℤ))
⊢ ∃g:ℕ||L1|| + ||L2|| ⟶ ℕ||L||. ∀i:ℕ||L1|| + ||L2||. ((g i) = if i <z ||L1|| then f1 i else f2 (i - ||L1||) fi  ∈ ℤ)
BY
{ (InstConcl [λi.if i <z ||L1|| then f1 i else f2 (i - ||L1||) fi  ] THENA Auto) }
1
1. [T] : Type
2. L1 : T List
3. L2 : T List
4. L : T List
5. f1 : ℕ||L1|| ⟶ ℕ||L||
6. f2 : ℕ||L2|| ⟶ ℕ||L||
7. increasing(f1;||L1||)
8. ∀j:ℕ||L1||. (L1[j] = L[f1 j] ∈ T)
9. increasing(f2;||L2||)
10. ∀j:ℕ||L2||. (L2[j] = L[f2 j] ∈ T)
11. ∀j1:ℕ||L1||. ∀j2:ℕ||L2||.  (¬((f1 j1) = (f2 j2) ∈ ℤ))
⊢ ∀i:ℕ||L1|| + ||L2||
    (((λi.if i <z ||L1|| then f1 i else f2 (i - ||L1||) fi ) i) = if i <z ||L1|| then f1 i else f2 (i - ||L1||) fi  ∈ ℤ)
Latex:
Latex:
.....assertion..... 
1.  [T]  :  Type
2.  L1  :  T  List
3.  L2  :  T  List
4.  L  :  T  List
5.  f1  :  \mBbbN{}||L1||  {}\mrightarrow{}  \mBbbN{}||L||
6.  f2  :  \mBbbN{}||L2||  {}\mrightarrow{}  \mBbbN{}||L||
7.  increasing(f1;||L1||)
8.  \mforall{}j:\mBbbN{}||L1||.  (L1[j]  =  L[f1  j])
9.  increasing(f2;||L2||)
10.  \mforall{}j:\mBbbN{}||L2||.  (L2[j]  =  L[f2  j])
11.  \mforall{}j1:\mBbbN{}||L1||.  \mforall{}j2:\mBbbN{}||L2||.    (\mneg{}((f1  j1)  =  (f2  j2)))
\mvdash{}  \mexists{}g:\mBbbN{}||L1||  +  ||L2||  {}\mrightarrow{}  \mBbbN{}||L||
      \mforall{}i:\mBbbN{}||L1||  +  ||L2||.  ((g  i)  =  if  i  <z  ||L1||  then  f1  i  else  f2  (i  -  ||L1||)  fi  )
By
Latex:
(InstConcl  [\mlambda{}i.if  i  <z  ||L1||  then  f1  i  else  f2  (i  -  ||L1||)  fi    ]  THENA  Auto)
Home
Index